2021
DOI: 10.1186/s12645-021-00086-8
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer drug delivery by novel drug-loaded chitosan-coated magnetic nanoparticles

Abstract: Background Breast cancer is one of the most challenging cancers among women which is considered one of the most lethal cancers to this date. From the time that cancer has been discovered, finding the best therapeutic method is still an ongoing process. As a novel therapeutic method, nanomedicine has brought a vast number of materials that could versatilely be used as a drug carrier. The purpose of this study is to develop a novel black pomegranate peel extract loaded with chitosan-coated magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 85 publications
1
28
0
Order By: Relevance
“…The viability of cells was measured on a microplate reader at an absorbance wavelength of 570 nm using the reference standard at 630 nm . Further, a linear regression equation was used to determine the IC 50 value and percentage cell viability …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viability of cells was measured on a microplate reader at an absorbance wavelength of 570 nm using the reference standard at 630 nm . Further, a linear regression equation was used to determine the IC 50 value and percentage cell viability …”
Section: Methodsmentioning
confidence: 99%
“…60 Further, a linear regression equation was used to determine the IC 50 value and percentage cell viability. 69 Analysis of Apoptotic Activity. To study apoptosis, 3 × 10 5 cells per well (A549, A431, and HL60) were seeded in six-well plates and incubated for 24 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Chitosan, an economical multifunctional polymer with several desirable physicochemical and biological characteristics, obtainable from seafood waste, has been investigated for use in agriculture, pharmacy, and biomedicine. In the past two years, research has focused on exploring the potential of chitosan application, especially within the areas of the food industry [173][174][175], health care [176][177][178], and environmental application [179,180]. Through its numerous functional groups, chitosan allows for diverse forms of interaction, such as ionic hydrogen bonding, which is one of the reasons for its appeal in a variety of applications [181,182].…”
Section: Current Research Trends On Chitosanmentioning
confidence: 99%
“…Chitosan is one of the popular materials for the development of therapeutic and diagnostic applications and also in the area of nanomedicine [176][177][178] to improve drug delivery efficiency and drug therapeutic index [187,188]. Nanoparticle products for the diagnosis of cancer imaging as well as for pharmacotherapeutic treatment have been established, and the fabrication of nanoparticle systems by applying chitosan has been explored.…”
Section: Current Research Trends On Chitosanmentioning
confidence: 99%
“…Their findings revealed that anti-EGFR aptamer-conducted lipid transporters could be a promising nanocarrier device for RNA intervention and fluorescence imaging of these highly invasive BC cells [ 46 , 76 ]. In 2021, Taherian and coworkers characterized chitosan-coated magentic NPs and examined their efficiency as black pomegranate peel extract (PPE) transporters [ 77 ]. Their results indicated that the drug-loaded NPs can eradicated cancerous cells significantly compared to that of free drug alone.…”
Section: Introductionmentioning
confidence: 99%